Composite of biomass and lead resistent Aspergillus oryzae for highly efficient aqueous phase Pb(II) adsorption. Issue 6 (15th April 2017) - Ji, Zehua; Feng, Chongling; Wu, Xiaofu; Li, Yanfeng; Li, Liugang; Liu, Xiangjun
Abstract : In this research, compound biosorbent peanut shell‐HA (PSH) and millet chaff‐HA (MCH), which were composited by peanut shell (PS) and millet chaff (MC) with lead resistent Aspergillus oryzae (HA), respectively, were used to remove Pb 2+ from aqueous solution. The characterize of biosorbents were analyzed by FTIR and SEM. Batch experiments were performed to evaluate the effect of pH, biosorbent concentration, initial Pb 2+ concentration and contact time on the Pb 2+ removal. The results indicated that the functional groups and surface morphology of PSH and MCH were significantly different after compound procedures. The maximum adsorption capacity q m of PSH and MCH were 43.09% and 83.21% higher than PS and MC, respectively. Meanwhile, the compound biosorbent showed a significant adsorption advantage at the low pH and more efficient in adsorption compared to pristine materials. The adsorption isotherms and kinetics studies demonstrated that the adsorption process can be well fitted by the Langmuir and pseudo‐second‐order model, respectively. Fixed‐bed experiments showed that the MCH possesses stronger fixed bed adsorption capacity ( q exp[MCH] =8.30 mg g −1, q exp[PSH] =7.13 mg g −1 ) and shorter height of mass transfer zone ( H [MCH] =6.96 cm, H [PSH] =16.56 cm) than PSH. The compound biosorbents performs better than pristine materials with higher adsorption capacity. This study provides a promising strategy for manufacture of new biosorbent. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 1658–1666, 2017